The antiviral potential of itaconate and its derivative 4-Octyl itaconate against RNA viruses - Weiss, Hauke Johannes (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2023)
Itaconate is a Krebs cycle derived metabolite which has been shown to have anti-inflammatory properties. This specially applies to derivatives of itaconate, notably the cell permeable analogue 4-octyl itaconate (4-OI) which has been extensively studied in models of inflammation. Itaconate and 4-OI have been shown to be antiviral against Zika virus, Influenza A virus (IAV) and Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here itaconate and 4-OI have been examined as potential antiviral agents for IAV and SARS-CoV-2. 4-OI inhibited replication of both SARS-CoV-2 and IAV in vitro and in vivo. In lung epithelial cells, 4-OI potently blocked expression of the SARS-CoV-2 uptake receptor, Angiotensin-converting enzyme 2 (ACE2), reducing ACE2 dependent uptake. For IAV, 4-OI inhibited replication of the virus by restricting nuclear export of viral ribonucleoproteins (vRNPs), a key step in the IAV replication cycle. This nuclear retention was achieved by deactivation and subsequent degradation of Chromosomal Maintenance 1 protein (CRM1), also known as Exportin 1 (XPO1), a host cell protein exploited by IAV during replication. 4-OI-mediated deactivation of CRM1 resulted in accumulation of the IAV nucleoprotein (NP), the Rev protein of Feline Immunodeficiency Virus (FIV), as well as the natural CRM1 cargos RAN Binding Protein 1 (RanBP1), p53 and p65 in the nucleus of treated cells. Further mechanism of action studies revealed that, similar to known CRM1 inhibitors, 4-OI modified a key cysteine in the cargo binding pocket of CRM1 at position 528 through an alkylation reaction called 2,3-dicarboxypropylation. Subsequent studies in a cell line in which the cysteine at position 528 in CRM1 was substituted by a serine, confirmed that modification of this residue was indeed the cause of the observed inhibitory effect induced by 4-OI on CRM1 function. Overall, this study demonstrates a mechanism through which 4-OI directly interferes with SARS-CoV-2 infection, and the replication cycle of CRM1-dependent viruses, which contributes to our understanding of the antiviral and anti-inflammatory properties of this multifaceted immuno-metabolite.
APPROVED